Infant feeding practice on growth velocity in 4-6 month-olds - Joko Kurniawan; Alifah Anggraini; Madarina Julia (Paediatrica Indonesiana, 2018)
Background In developing countries, 5-10% of infants suffer from failure to thrive. Adequate feeding is the most crucial factor for optimal growth in early life. Objective To assess the differences in growth velocity at 4 to 6 months of age, based on the infant feeding practices. Methods This cross-sectional study involving 4 to 6 month-old babies from 6 public health centres in Yogyakarta was performed from August to November 2016. Data on body weight, and growth velocity as they related to weight at birth were collected. Subjects were divided into groups according to their feeding practices. Results Of 173 subjects, 130 (75%) infants were exclusively breastfed, 19 infants (11%) were given breast milk and formula, 14 (8%) infants were given breast milk and complementary food (8%), and 10 (6%) infants were given formula and complementary food. The mean growth velocity z-scores by group were as follows: exclusively breastfed 0.04 (SD 1.15) (95%CI -0.16 to 0.24), breast milk and formula -0.61 (SD 0.84) (95%CI -1.01 to -0.21), breast milk and complementary food -0.69 (SD 1.14) (95%CI -1.35 to -0.04), formula and complementary food 0.23 (SD 1.50) (95%CI: -0.84 to 1.31). The mean difference in growth velocity between the exclusively breastfed vs. breast milk and formula groups was 0.65 (SD 0.28) (95%CI: 0.10 to 1.20; P=0.02); vs. breast milk and complementary food was 0.73 (SD 0.32) (95%CI: 0.10 to 1.37; P=0.02); and vs. formula and complementary food was -0.19 (SD 0.37) (95%CI: -0.93 to 0.55; P=0.61). Conclusion Exclusively breastfed have the most optimal growth velocity compared to infants who experience other feeding practices.